Desenvolvimento do sentido de número em crianças de 4 a 5 anos e 11 meses - Pagani, Karla Bertacini Brassi (Universidade Federal de São Carlos, 2024)
This study refers to a master's degree research, linked to the Professional Postgraduate Program in Education (PPGPE) at the Federal University of São Carlos (UFSCar), with the main objective of analyzing the interactions and representations of Early Childhood Education children, with a specific age between 4 to 5 years and 11 months, in mathematical exploration situations developed from the perspective of number sense. For the discussion, reflections on multiple functions of the number in different contexts and that the social use of this demarcates forms of representation that give senses to children's learning, starting from pre-school. The methodology is part of the field of qualitative studies, of an interpretative-analytical nature, in which, from the intervention research, the researcher is the teacher of the class investigated. In this way, the proposal was to put myself in the place of a teacher-researcher about the implications of teaching practice in situations designed to understand number sense in the class. The data production instruments were: observation, intervention and video recording of dialogues created with children based on the scenarios established for this purpose. In summary, due to little exploration of the theme of Mathematics in Early Childhood Education, evidenced in previous works, the results obtained may serve as support for professionals who work with this age group, helping them to create rich, meaningful and challenging learning environments. As a central result of the reflections expressed in the research, we constituted a Product Educational in the form of an e-book entitled "Number Sense with Children in Preschool Age: 4 Experiences for Mathematical Exploration", which we consider relevant with a view to raising performance indicators for early childhood educators.
Development of number sense in children aged 4 to 5 years and 11 months
Keywords: Educação infantil; Educação matemática na infância; Sentino de número; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO